2019
DOI: 10.3340/jkns.2019.0140
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Treatment Outcome of Intracranial Aneurysms in Children and Adolescents

Abstract: Objective Intracranial aneurysms are not common in young age patients. We sought to find the characteristics of the intracranial aneurysms in patients under 20 years of age. Methods We reviewed 23 consecutive patients ≤20 years of age treated for their intracranial aneurysms during the period from 1995 to 2017. From medical records and imaging studies, we gathered data on age, sex, presentation, associated medical condition, location and characteristics of aneurysms, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
5
14
0
Order By: Relevance
“…In our sample, giant aneurysms were found in ~ 27% of the cases, compatible with the 6-40% found in other series [2,7,8,13,22]. Regarding the location of the aneurysms, the ICA was the most common site (53%), as reported in several series [7,13,15], although some authors found MCA predominance [3,4]. Regarding the morphology, although most aneurysms were saccular and located in the anterior circulation, the rates of fusiform aneurysms (13%) and posterior circulation aneurysms (27%) are similar to literature, and higher when compared with adult series [1,2,3,15].…”
Section: Characteristics In Young-age Patientssupporting
confidence: 91%
See 1 more Smart Citation
“…In our sample, giant aneurysms were found in ~ 27% of the cases, compatible with the 6-40% found in other series [2,7,8,13,22]. Regarding the location of the aneurysms, the ICA was the most common site (53%), as reported in several series [7,13,15], although some authors found MCA predominance [3,4]. Regarding the morphology, although most aneurysms were saccular and located in the anterior circulation, the rates of fusiform aneurysms (13%) and posterior circulation aneurysms (27%) are similar to literature, and higher when compared with adult series [1,2,3,15].…”
Section: Characteristics In Young-age Patientssupporting
confidence: 91%
“…The aneurysms in childhood have a higher proportion of giant, fusiform and posterior circulation aneurysms than in adults [2,7,8,13,15,17]. In our sample, giant aneurysms were found in ~ 27% of the cases, compatible with the 6-40% found in other series [2,7,8,13,22].…”
Section: Characteristics In Young-age Patientssupporting
confidence: 87%
“…Regarding locations, the authors reported a higher proportion of posterior circulation [1, 4, 8, 9, 15] and ICA terminus [11, 15] aneurysms in children than in adults [1, 3], as well as dissecting aneurysms [3, 15] and giant lesions [3-5, 7-10]. In this series, 24% of the lesions ( n = 4) were in the posterior circulation, and 18% ( n = 3) in ICA terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Brain aneurysms affect almost exclusively the adult population [1], and its incidence in children is rare [1][2][3][4][5][6][7][8][9][10], accounting for less than 5% of all aneurysms [1-3, 5, 7, 8, 11, 12]. Also, compared to adults, they are more complex [4,10] and differ in location, morphological characteristics, the presentation, and outcome [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 To date, most reports of pediatric aneurysms consist of case reports and small case series. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Most large series in the last 15 years reported on an average of 39 patients. We previously presented a series of 19 patients treated at our institution from 1991 to 2004 over the course of 13 years.…”
mentioning
confidence: 99%